The Relationship between Strategic Awareness and Organizational Culture: An Analytical Study in the General Directorate of Training and Qualification / Ministry of Interior - Muhammad Bahloul , Basim; Abdel-Wadoud Taher, Adel (Journal of Economics and Administrative Sciences, 2024)
The main purpose of this research is to test the relationship between strategic awareness and organizational culture in the General Directorate of Training and Qualification/ the Ministry of Interior. In view of the importance of the research topic and sample for the researched directorate, the researcher adopted the descriptive analytical approach using the questionnaire as a primary tool for data collection. The research sample is represented by the heads of departments division directors, and training officers in the directorate. The sample was limited to 119 officers out of a total of 181 officers. The questionnaire consists of 57 items, and answers were analyzed using the statistical program (SPSS). As for the practical effects of the research, it was found that the main hypothesis was rejected, and the alternative hypothesis was accepted, which indicates the existence of a correlation between strategic awareness and organizational culture. One of the important recommendations is to develop a spirit of cooperation among the employees of the directorate and provide them with opportunities to participate in expressing their opinions in solving the problems facing the directorate and enhancing the performance of the employees. Continuous guidance and follow-up by the directorate is also recommended to bridge the gap between planning and implementation, by monitoring the implementation of annual plans and ensuring their quality.